The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision - Costa, Wilson J.e.m. (Zootaxa, 2006)
The annual fish genus Austrolebias is redefined to include species previously placed in Megalebias, and is revised based on characters of osteology, external morphology, the latero-sensory system and color patterns. Monophyly of Austrolebias is supported by the absence of scales between the corner of the mouth and anterior portion of the preopercular region and ventral portion of the opercular region, a deep urohyal, presence of a dark gray supraorbital spot, dorsal and anal fins rounded in males, a long urogenital papilla in males, and reduced ventral process of the angulo-articular. Thirty-eight species are recognized as valid: A. cinereus, A. robustus, A. nonoiuliensis, and A. bellottii, from the lower de La Plata River basin and adjacent areas; A. varzeae, A. melanoorus, A. apaii Costa, Laurino, Recuero & Salvia, new species, A. alexandri, A. ibicuiensis, A. affinis, A. duraznensis, and A. periodicus, from the Uruguay River basin; A. nigripinnis and A. elongatus n. comb., from both the lower de La Plata and Uruguay river basins; A. viarius, A. univentripinnis, A. charrua, A. minuano, A. adloffi, A. nigrofasciatus, A. nachtigalli Costa & Cheffe, new species, A. salviai Costa, Litz & Laurino, new species, A. luteoflammulatus, A. gymnoventris, A. jaegari, A. cheradophilus n. comb., A. wolterstorffi n. comb., and A. prognathus n. comb., A. cyaneus, and A. litzi new species, from the dos Patos lagoon system and adjacent areas to the south; A. vazferreirai, A. arachan, and A. juanlangi Costa, Cheffe, Salvia & Litz, new species, from both the dos Patos lagoon system and Uruguay River basin; A. paranaensis, new species, A. vandenbergi, A. monstrosus n. comb., A. patriciae, from the Paraguay and middle Paraná river basins; and, A. carvalhoi, from the rio Iguaçu basin. A key to the identification of species is provided. A phylogenetic hypothesis based on morphology for species of Austrolebias is compared to a recent hypothesis based on molecular data, demonstrating partial or full congruence between the two sets of characters.